Use of Social Media in the Convenient 2020 Election of Regent and Deputy Regent Pandemic Time of Covid-19 in Majene District - Muhammad (East Asian Journal of Multidisciplinary Research, 2023)
This study is measure how the use of social media in elections regent and deputy regent simultaneously 2020 during the Covid-19 pandemic, especially in the district Majene. Theory used _ is theory participation Samuel Huntington's politics divided participation into two parts that is participation conventional and non- conventional. Study done using survey method to the 400 respondents who entered to in must vote in the 2020 local elections with a 4% margin of error. Result of study show that public Majene is very adaptive with adjustments form participation politics at the Pilkada momentum in the middle the covid-19 pandemic . Scalable from survey that public take advantage of social media in do update information related local election Facebook is a social media with utilization highest society _ followed whatsapp , Instagram, youtube, tiktok, and twitter. Utilization the maximized For know information organizer election, you know record trail and candidate program until know activity candidate during the campaign period during the Covid-19 pandemic.